2021
DOI: 10.1111/epi.16870
|View full text |Cite
|
Sign up to set email alerts
|

Social outcome and psychiatric comorbidity of generalized epilepsies – A case‐control study

Abstract: Objective: To investigate social outcome and psychiatric comorbidity of patients with idiopathic/genetic generalized epilepsies (IGEs) and its subtypes (epilepsy with generalized tonic-clonic seizures alone [EGTCS], juvenile absence epilepsy [JAE], and juvenile myoclonic epilepsy [JME]). Methods: A cohort of 402 adult patients with IGE from the Danish island Funen was matched with 4020 randomly selected geography-, age-, and sex-matched controls via the Danish Civil Registration System. Based on register data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
3
19
0
1
Order By: Relevance
“…High-burden of disease was also associated with absence and myoclonic seizures indicative for JME. This is in keeping with a recent register-based study from the same cohort reporting a substantially increased risk of psychiatric disease in IGE and particular patients with JME [5,28]. The association of self-reported JME and burden of disease (uncorrected p-value: 0.02, non-significant after correction for multiple testing, Table 2) has to be interpreted with some care given that the self-reported syndrome diagnosis did not show an optimal concordance with the specialist evaluation, likely due to the well-known difficulties associated with the diagnosis of JME [29].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…High-burden of disease was also associated with absence and myoclonic seizures indicative for JME. This is in keeping with a recent register-based study from the same cohort reporting a substantially increased risk of psychiatric disease in IGE and particular patients with JME [5,28]. The association of self-reported JME and burden of disease (uncorrected p-value: 0.02, non-significant after correction for multiple testing, Table 2) has to be interpreted with some care given that the self-reported syndrome diagnosis did not show an optimal concordance with the specialist evaluation, likely due to the well-known difficulties associated with the diagnosis of JME [29].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies found more psychiatric comorbidities among patients with IGE than among healthy controls [5,34,35]. We found similar results in our psychiatric scores, where BIS-8, SAPAS-AV, and MDI all were higher in our patients compared to those of healthy populations from other studies [23,26,27].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations